Agricultural Extension Perceptions of Widyaiswara Sapa Kostratani (WISATANI) E-Learning Program - Retno Hermawan; Adhis Millia Windhy (Politeknik Pembangunan Pertanian Malang, 2022)
Agricultural extension workers have limitations in participating in direct learning (face to face) in order to increase competence. E-Learning is a learning concept that utilizes information technology. Binuang Agricultural Training Center implements E-Learning Widyaiswara Sapa Kostratani (WISATANI), a synchronous learning program to support the improvement of Agricultural Extension Cognitive competence. To support the improvement of the Wisatani program, it is necessary to know the perceptions of the Agricultural Extension Officers who participated in the Wisatani e-Learning program. This research was conducted using the Quantitative Descriptive method with the purposive sampling method for Purnawidya E-Learning Wisatani. The result of the research is that the Wisatani E-Learning Program has the value of the benefits felt by the Agricultural Extension. The perceived benefit value is in the form of supporting the addition of knowledge for Purnawidya. But instead of that it is necessary to diversify the method of delivering material, not only in Lectures and Discussions but needs to be improved with Video Tutorials and Hands-on Practice.